Comparison of ISSR and AFLP markers in assessing genetic diversity among Nettle (Urtica dioica L.) populations. - Mostafa Haghpanah; Seyed Kamal Kazemitabar; Seyed Hamidreza Hashemi; Seyed Mohammad Alavi (Journal of Plant Molecular Breeding, 2016)
Urtica dioica is an important medicinal plant which is widely distributed in Mazandaran province (North of Iran). In this study for the ﬁrst time Ampliﬁed Fragment Length Polymorphism (AFLP) and Inter-simple Sequence Repeat (ISSR) markers were used for detection of genetic polymorphism in Mazandaran nettle. Ten AFLP primer combinations and seventeen ISSR markers were utilized. AFLP produced 830 scorable bands out of which 90.21% were polymorphic. ISSR primers ampliﬁed 234 bands, 181 being polymorphic (77.3%). Average heterozygosity for AFLP and ISSR markers were 0.25, 0.23 respectively. Marker Index obtains 22.25 for AFLP and 15.57 for ISSR. The number of cluster computed was same for both molecular makers but location of samples in branch were different. The total compare of these two marker systems shown AFLP marker was a useful tool for detection of U. dioica’sgenetic diversity. This plant is very variable and is genetically distinct in east, west and north of Mazandaran.